Growth data of outlying plantations allows benchmarking the tolerance to climate extremes and drought stress in the European larch - Camarero, Jesús Julio; Gazol, Antonio; Valeriano, Cristina; Vergarechea, Marta; Cattaneo, Nicolás (Frontiers in Plant Science, 2024)
Plantations located outside the species distribution area represent natural experiments to assess tree tolerance to climate variability. Climate change amplifies warming-related drought stress but also leads to more climate extremes. We studied plantations of the European larch (Larix decidua), a conifer native to central and eastern Europe, in northern Spain. We used climate, drought and tree-ring data from four larch plantations including wet (Valgañón, site V; Santurde, site S), intermediate (Ribavellosa, site R) and dry (Santa Marina, site M) sites. We aimed to benchmark the larch tolerance to climate and drought stress by analysing the relationships between radial growth increment (hereafter growth), climate data (temperature, precipitation, radiation) and a drought index. Basal area increment (BAI) was the lowest in the driest site M (5.2 cm 2 yr -1 ; period 1988-2022), followed by site R (7.5 cm 2 yr -1 ), with the youngest and oldest and trees being planted in M (35 years) and R (150 years) sites. BAI peaked in the wettest sites (V; 10.4 cm 2 yr -1 ; S, 10.8 cm 2 yr -1 ). We detected a sharp BAI reduction (30% of the regional mean) in 2001 when spring-to-summer conditions were very dry.In the wettest V and S sites, larch growth positively responded to current March and June-July radiation, but negatively to March precipitation. In the R site, high April precipitation enhanced growth. In the driest M site, warm conditions in the late prior winter and current spring improved growth, but warm-sunny conditions in July and dry sunny conditions in August reduced it. Larch growth positively responded to springsummer wet conditions considering short (1-6 months) and long (9-24 months) time scales in dry (site M) and wet-intermediate (sites S and R) sites, respectively. Larch growth is vulnerable to drought stress in dry slow-growing plantations, but also to extreme spring wet-cloudy events followed by dry-hot conditions in wet fast-growing plantations.